2004
DOI: 10.1111/j.0818-9641.2004.01285.x
|View full text |Cite
|
Sign up to set email alerts
|

Shaping of adaptive immune responses to soluble proteins by TLR agonists: A role for IFN‐α/β

Abstract: Summary Toll-like receptors (TLR) are believed to play a major role in the recognition of invading organisms, although their ability to shape immune responses is not completely understood. Our aim was to investigate in vivo the effect of different TLR stimuli on the generation of antibody responses and the induction of CD8 + T-cell crosspriming after immunization with soluble protein antigens. While all TLR agonists tested elicited the production of immunomodulatory cytokines, marked differences were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
70
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 18 publications
4
70
2
Order By: Relevance
“…Durand et al (5) demonstrated that LPS adjuvant activity was largely dependent on the IFNα/β signaling pathway. The induction of functional cross-priming to soluble protein antigens by LPS in IFNα/β-deficient mice was abrogated in the absence of IFNα/β signaling [37]. The results of our study suggest that KDO 2 linked to lipid A is crucial for TNFα induction from human macrophages, but is not required for retaining adjuvant activity in mice.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Durand et al (5) demonstrated that LPS adjuvant activity was largely dependent on the IFNα/β signaling pathway. The induction of functional cross-priming to soluble protein antigens by LPS in IFNα/β-deficient mice was abrogated in the absence of IFNα/β signaling [37]. The results of our study suggest that KDO 2 linked to lipid A is crucial for TNFα induction from human macrophages, but is not required for retaining adjuvant activity in mice.…”
Section: Discussionmentioning
confidence: 59%
“…TNFα induction is MyD88-dependent [44]. In support, IL-12p70 production in mice by different microbial ligands does not correlate with IgG2a induction [37]. Macrophages exposed to unglycosylated meningococcal lipid A (kdtA) do release lower quantities of nitric oxide in a dose-dependent manner (Figure 2).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, the ability of DC to crosspresent exogenous model antigens such as OVA in the presence of TLR ligands to CD8 1 T cells has been shown to depend on IFN-a/b receptor (IFN-a/bR) signaling. Thus, both MyD88 as well as type I IFN signaling has been shown to be important for the crosspresentation of exogenous model antigens [25][26][27][28][29].VLP as non-replicating antigens need to be cross-presented in order to prime CD8 1 T cells. We have previously shown that the immuno-dominant H-2D b restricted lymphocytic choriomeningitis virus (LCMV)-glycoprotein-derived peptide p33 coupled to VLP is efficiently cross-presented by both DC and macrophages.…”
mentioning
confidence: 99%
“…Furthermore, the ability of DC to crosspresent exogenous model antigens such as OVA in the presence of TLR ligands to CD8 1 T cells has been shown to depend on IFN-a/b receptor (IFN-a/bR) signaling. Thus, both MyD88 as well as type I IFN signaling has been shown to be important for the crosspresentation of exogenous model antigens [25][26][27][28][29].…”
mentioning
confidence: 99%